FRI0228 Cutaneous vasculitis as a presenting manifestation of neoplasia. (23rd January 2014) - Loricera, J.; Calvo-Río, V.; Ortiz-Sanjuán, F.; González-Lόpez, M.; Fernández-Llaca, H.; Rueda-Gotor, J.; González-Vela, M.; Mata-Arnáiz, C.; Martínez-Taboada, V.; Peña-Sagredo, J.; González-Gay, M.; Blanco, R.
Abstract : Background: Cutaneous Leukocytoclastic Vasculitis (CLV) may be associated with malignancies, and sometimes it behaves as a paraneoplastic syndrome. This association has been reported in a variable proportion of CLV patients (from 0 to 8%) depending on population selection. Objectives: Our aim was to assess the frequency and features of CLV associated to neoplasia in a wide and unselected series of CLV. Methods: Study of CLV associated to neoplasia in a serie of 565 patients diagnosed as having CLV in the Rheumatology and Dermatology Divisions from a University Hospital. Results: 11 out of 565 patients (1.95%) presenting with CLV were finally diagnosed as having an underlying malignancy (7 hematological/4 solid malignacies). In all of them, skin lesions were the first clinical manifestation. The median to the diagnosis of the malignancy from the onset of CLV was 17 days, (range 8–50). The most frequent skin lesions were palpable purpura (n=10), legs ulcers (n=2) and urticaria (n=1). Other manifestations were constitutional syndrome (n=7) and arthralgias and/or arthritis (n=3). There was no serious visceral vasculitic involvement. Cytopenia was frequently observed in the full blood cell count (n=9), especially in those cases of vasculitis associated to hematological malignancies (immature peripheral blood cells were observed in 4 cases). Immunological testing (ANA, Rheumatoid factor, C3, C4, and ANCA) were negative or within normal range in all cases. Six patients died due to the malignancy and 5 patients recovered following malignancy therapy. Conclusions: CLV presenting as a paraneoplastic syndrome is a rare condition. The most common underlying malignancy is generally hematological. The prognosis depends on the underlying neoplasia. Disclosure of Interest: None Declared